2005
DOI: 10.1002/ccd.20480
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endoscopic and macroscopic observations after crush stenting of coronary artery bifurcations in pigs

Abstract: The crush stent technique has recently been proposed to limit the development of restenosis between drug-eluting stents implanted at coronary artery bifurcations. We studied the stent expansion, apposition to the vessel, and aspect of the overlapping stents after in vivo crush stent implantation. Crush stent implantation was performed at coronary bifurcations in anesthetized swines. The treated sites were examined using intravascular ultrasound and a vascular endoscope. The stents removed from the vessel were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…Additional KB inflation has been reported to promote the stent apposition to the carina in the presence of narrow angles of bifurcation [13] and to lower the risk of restenosis [12,16]. However, even after KB inflation, incomplete stent crush or unsatisfactory stent apposition to the vessel at the ostium of the side branch have been observed in animal experiments [14] and in clinical intravascular ultrasound examinations [15]. The contributions of the 3D structure of the LMCA bifurcation to complicated stent expansions, stent deformities, and to the presence of unstented segments are not well understood.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Additional KB inflation has been reported to promote the stent apposition to the carina in the presence of narrow angles of bifurcation [13] and to lower the risk of restenosis [12,16]. However, even after KB inflation, incomplete stent crush or unsatisfactory stent apposition to the vessel at the ostium of the side branch have been observed in animal experiments [14] and in clinical intravascular ultrasound examinations [15]. The contributions of the 3D structure of the LMCA bifurcation to complicated stent expansions, stent deformities, and to the presence of unstented segments are not well understood.…”
Section: Discussionmentioning
confidence: 98%
“…The mechanisms of incomplete stent apposition at the ostium of the side branch include (a) distortion of the side branch stent at the distal carina, particularly likely in the presence of wide-angled bifurcation [13], (b) gradual crush of the side branch stent [14], (c) insufficient expansion of the side branch stent [15], and (d) fracture of the side branch stent [8,17]. In the present study, an unstented segment was also observed in the experiment using the 3D model of LMCA bifurcation, as well as in the two-dimensional model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the combination of crush stenting with final KB inflation might be expected to yield even better results. However, 75% of restenotic lesions in these studies were located at the ostium of the side branch [18][19][20][21]; this has been variously attributed to incomplete apposition between stent and vessel [12][13][14], under-expansion [21], and fracture of the side branch stent [22]. It has been shown that a wide (>708) bifurcation angle promotes the distortion of the side branch stent, which as a result, is not completely apposed to the vessel, even after KB inflation [12,13].…”
Section: Crush Stentingmentioning
confidence: 94%
“…Recent experimental studies have demonstrated that a wide-angle bifurcation [12,13], the three-dimensional (3D) vascular structure [13,14], gradual crush [14] and stent overlap or crossing in the distal LMCA [13], can prominently contribute to incomplete apposition after double stenting. However, the impacts of spatial distribution of stent expansion and distortion of the native 3D structure have not yet been completely clarified.…”
Section: Introductionmentioning
confidence: 99%